Analysis and implementation of 3D bandpass frequency selective structure with high frequency selectivity. Issue 5 (1st March 2017) - Tao, Keya; Li, Bo; Tang, Yiming; Zhang, Ming; Bo, Yaming
Abstract : A novel 3D frequency selective structure (FSS), exhibiting bandpass filtering response with high frequency selectivity, is presented. In each unit cell, multiple resonators are constructed to provide multiple transmission zeros/poles. By establishing an equivalent circuit model, it is obtained that the transmission poles in the passband are produced by a short‐circuited resonator and an open‐circuited resonator, and the transmission zeros close to the passband are attributed to the fundamental and spurious resonant frequencies of another short‐circuited resonator. To implement it in high frequencies, multi‐layer printed circuit board technology is introduced, where several replacements are carried out. The measured results show good agreement with simulations. Furthermore, the proposed FSS exhibits stable performance with incident angles increased from 0 to 50°.